Klein-Gordon-Maxwell System with Partially Sublinear Nonlinearity - Li, Lin; Chen, Shang-Jie; Song, Shu-Zhi (Communications in Mathematics and Applications, 2018)
In this paper we shown that a class of sublinear Klein-Gordon-Maxwell system has infinitely many solutions by using a critical point theorem established by Liu and Wang and Moser iteration method.